Improved high-performance fully non-inductive discharge by optimizing the fast-ion confinement on EAST. (30th October 2019) - Huang, J.; Qian, J.P.; Garofalo, A.M.; Gong, X.Z.; Wu, C.R.; Chang, J.F.; Zhang, J.; Du, H.F.; Wu, M.Q.; Hao, B.L.; Yu, L.M.; Zhang, X.M.; et al.
Abstract: The attainment of long-pulse, high-performance, fully non-inductive plasma is one of the major scientific objectives of EAST, using the ITER-like tungsten upper divertor. Understanding and optimizing the fast-ion behaviors is the critical issue to extending the performance of EAST. Recently, using both neutral beam injection (NBI) and radio frequency (RF; low hybrid, electron cyclotron, and ion cyclotron) heating, fully non-inductive high- β P scenarios with extension of fusion performance at high density and low rotation have been achieved, with β P up to 2.5, β N up to 2.0, H 98 y 2 > 1.1, and bootstrap current fraction ( f BS ) up to 50%. For previous long-pulse H-mode plasma at medium density, when NBI is added into RF plasma, β p is increased from 1.2 to 2.0 compared with RF-only discharges. In fact, f BS for both discharges is nearly the same, at 22%. Analysis shows that the increase in β p is mostly due to fast ions which do not contribute significantly to the neoclassical bootstrap current. Thus, to obtain high-performance plasmas with improved bootstrap current fraction, key parameters (e.g. density, beam energy, etc.) must be further optimized. Experimental results show that high density improves bootstrap fraction also by reducing fast-ion slowing-down time and loss. The lower beam energy also mitigates fast-ion loss, which is better for heating and CD performance. The extension of high-performance, fully non-inductive experiments on EAST at high density and zero/low NBI torque can potentially offer unique contributions towards ITER and CFETR.